Policy Implementation on Implementation of Society Economic Empowerment Fund Utilization - David Wilfrid Rihi; Agus Suryono; Romy Hermawan (Sekolah Pascasarjana Universitas Brawijaya, 2019)
The society economic empowerment program in Kupang City aims to improve the economic structure and the giving of productive economic business capital which is in a small scale in accordance with the potential in the regency level, the target of which is the society who has the individual business in a small scale which has run. This research would like to describe and analyze the policy implementation on society economic empowerment fund utilization in the Kupang City Regional Development Planning Agency and the Society Empowerment Institution.The research method used in this research was descriptive research method with qualitative approach and spiral data analysis proposed by Creswell. The research result showed that the society economic empowerment program had not been able to empower the entire potentials which were available in society.